2014
DOI: 10.1016/j.celrep.2013.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Inference of Tumor Evolution during Chemotherapy by Computational Modeling and In Situ Analysis of Genetic and Phenotypic Cellular Diversity

Abstract: SUMMARY Cancer therapy exerts a strong selection pressure that shapes tumor evolution, yet our knowledge of how tumors change during treatment is limited. Here we report the analysis of cellular heterogeneity for genetic and phenotypic features and their spatial distribution in breast tumors pre- and post-neoadjuvant chemotherapy. We found that intratumor genetic diversity was tumor subtype-specific and it did not change during treatment in tumors with partial or no response. However, lower pre-treatment genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
222
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(239 citation statements)
references
References 50 publications
10
222
3
2
Order By: Relevance
“…This is of particular relevance for cancer treatment, as most patients will 8 eventually succumb to the disease owing to the appearance of resistant tumour subclones. Despite the considerable clinical impact of tumour heterogeneity 15 , little is known about how it affects response to cancer therapy and how it may change during treatment at both the genomic and the phenotypic levels [16][17][18][19][20] . These issues highlight the need for preclinical models that capture the heterogeneous nature of human cancers and their on-going evolution.…”
mentioning
confidence: 99%
“…This is of particular relevance for cancer treatment, as most patients will 8 eventually succumb to the disease owing to the appearance of resistant tumour subclones. Despite the considerable clinical impact of tumour heterogeneity 15 , little is known about how it affects response to cancer therapy and how it may change during treatment at both the genomic and the phenotypic levels [16][17][18][19][20] . These issues highlight the need for preclinical models that capture the heterogeneous nature of human cancers and their on-going evolution.…”
mentioning
confidence: 99%
“…Interestingly, recent genomic profiling studies 24, 25, 26, 27, 28, 29, 30, 31 suggested a substantial degree of intra‐ and inter‐tumour heterogeneity fuelling selection processes during evolution of breast cancer 32, 33, which may complicate prognostication as well as prediction and impede cancer precision medicine approaches 34. In this context, it is worth recalling that just as the molecular phenotype, the morphological phenotype of the tumour, including tumour grade and tumour size is essentially a result of accumulated genetic aberrations over time, thereby reflecting tumour evolution at the phenotypic level.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26]57,73 Thus, the genome theory calls into question the current standard protocols of chemotherapy, as drug intervention could paradoxically promote cancer evolution when applied in the wrong phase. 75,76 Therapeutic strategies should include the aim to reduce system stress to avoid triggering fast cancer evolution.…”
Section: Discussionmentioning
confidence: 99%